2012
DOI: 10.1073/pnas.1115796109
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous archaeal ATP synthase concurrently coupled to Na + and H + translocation

Abstract: ATP synthases are the primary source of ATP in all living cells. To catalyze ATP synthesis, these membrane-associated complexes use a rotary mechanism powered by the transmembrane diffusion of ions down a concentration gradient. ATP synthases are assumed to be driven either by H + or Na + , reflecting distinct structural motifs in their membrane domains, and distinct metabolisms of the host organisms. Here, we study the methanogenic archaeon Methanosarcina acetivorans using assays of ATP hydrolysis and ion tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 41 publications
9
104
0
Order By: Relevance
“…All c-rings known to be physiologically coupled to transmembrane Na + gradients can also bind H + , although functional coupling to H + (i.e., catalytic activity) has been observed typically only in in vitro conditions where the concentration of Na + is sufficiently low, e.g., less than 50 μM at pH 7 (39). [Thus, far, only the ATP synthase from Methanosarcina acetivorans has been observed to mediate Na + and H + permeation concurrently in physiological conditions (17).] Nevertheless, DCCD-labeling assays of Na + -coupled c-rings have clearly demonstrated that a competition between H + and Na + exists in a broader concentration range (40,41).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All c-rings known to be physiologically coupled to transmembrane Na + gradients can also bind H + , although functional coupling to H + (i.e., catalytic activity) has been observed typically only in in vitro conditions where the concentration of Na + is sufficiently low, e.g., less than 50 μM at pH 7 (39). [Thus, far, only the ATP synthase from Methanosarcina acetivorans has been observed to mediate Na + and H + permeation concurrently in physiological conditions (17).] Nevertheless, DCCD-labeling assays of Na + -coupled c-rings have clearly demonstrated that a competition between H + and Na + exists in a broader concentration range (40,41).…”
Section: Resultsmentioning
confidence: 99%
“…In previous theoretical studies, we have addressed this question for the family of ion-motive ATPases (17,29,30), which comprises eukaryotic and prokaryotic ATP synthases, as well as vacuolar ion pumps. In these multicomponent enzymes, a membrane-embedded substructure known as the rotor ring can revolve around its axis, relative to the rest of the protein's membrane domain.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Up to this point, based on studies of Methanobacteriales and Methanococcales methanogens, it was thought that all cytochrome-deficient hydrogenotrophic methanogens conserve energy using a Na + transmembrane chemiosmotic gradient, which is generated by tetrahydromethanopterin S-methyltransferase (Mtr) and consumed by a Na + -translocating ATP synthase (Schlegel and Müller, 2013). According to the new hypothesis, Methanomicrobiales members are expected to generate a H + gradient using Mtr (as supported by previous analyses of the MtrE subunit; Bräuer et al, 2015), and consume the H + gradient, thus generating ATP, using a H + /Na + promiscuous ATP synthase (Schlegel et al, 2012;Bräuer et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…Very interesting was the observation that some ATP synthases are capable of simultaneously translocate Na 1 and H 1 . Such an example is the enzyme from Methanosarcina acetivorans, and its coupling mechanism was suggested to be an adaptation to overcome the weak energy gain resulting from methanogenesis (50). The involvement of the two coupling ions concurrently has also been observed in some cation/solute symporters (as described below for the symporter CitS) (51).…”
Section: The Possibility Of Na 1 Being a Coupling Ion In Complex Imentioning
confidence: 99%